Internet of Things(IoT): Architecture, Challenges and Issues - Dimple Rani, Seema Grewal, Malika Bhiyana, Ashok, Ravi Kumar Barwal (International Journal of Advanced Science and Technology, 2020)
The speedy developments of current technology is largely dependent on the IoT and it is expect that it will plays an crucial role in the days to come. Many researchers focus on identifying the issues and problems involve in the designs and implementations of IoT. One of the many important issues is the lack of multiple language , protocol and policies and the lack of IQ that makes it work best for an IoT. There is no single classification system; This changed due to the size of the joint. There is no problem in design measurement, analysis and evaluation of other technical aspects to demonstrate and overcome it by demonstrating technical skills.